Immobilized nitrifying bacterial consortium for improving water quality, survival and growth of Penaeus monodon Fabricius 1798 postlarvae in hatchery system - Natnan, Maya Erna; Banerjee, Sanjoy; Khatoon, Helena; Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah (Asian Fisheries Society, 2013)
The exposure of shrimp postlarvae (PL) to toxic compounds such as ammonia leads to stress, diseases and mortality. In this study, a consortium of immobilized nitrifying bacteria M1 was tested for its efficacy in reducing total ammonia nitrogen (TAN) and nitrite nitrogen (NO2-N) so as to improve the survival and growth of Penaeus monodon Fabricius 1798 PL in hatchery system. The immobilized nitrifying bacterial consortium consisted of Pseudomonas aeruginosa, Pseudomonas stutzeri and Nocardiodes albus. There were three treatments, i.e., 1) tanks with beads containing immobilized nitrifying bacteria (106 cfu.mL-1), 2) tanks with beads without nitrifying bacteria, 3) tanks with 50% water exchange on alternate days (no nitrifying bacteria and beads), and 4) control tanks (no water exchange and without treatment). Results showed that tanks treated with immobilized bacteria were able to maintain TAN and NO2-N below 0.5 mg.L-1. In addition, shrimp PLs in tanks treated with immobilized bacteria had significantly (P<0.05) higher survival rate (72.44%) and specific growth rate (12.86%) compared to other treatments. This technology of using immobilized nitrifying bacteria should be further explored for use on a commercial scale for improving water quality, survival and growth of cultured shrimp PLs in hatcheries.